Atrial fibrillation ablation in patients with transthyretin cardiac amyloidosis. Issue 2 (14th November 2019) - Donnellan, Eoin; Wazni, Oussama; Kanj, Mohamed; Elshazly, Mohamed B; Hussein, Ayman; Baranowski, Bryan; Hanna, Mazen; Patel, Divyang; Trulock, Kevin; Martyn, Michael; Menon, Venu; Saliba, Walid; et al.
Abstract: Aims: Atrial fibrillation (AF) occurs in as many as 70% of patients with transthyretin cardiac amyloidosis (ATTR CA). The aim of our study was to investigate the impact of AF ablation on freedom from recurrent arrhythmia, hospitalization for AF or heart failure (HF), and mortality. Methods and results: This was a retrospective observational cohort study of 72 patients with ATTR CA and AF, of whom 24 underwent AF ablation and were matched in a 2:1 manner based on age, gender, ATTR CA stage, New York Heart Association functional class, ejection fraction, and date of AF diagnosis with 48 patients with ATTR CA and AF undergoing medical management. During a mean follow-up of 39 ± 26 months, 10 (42%) patients remained free of recurrent arrhythmia following ablation. Ablation was significantly more effective in those with Stage I or II ATTR CA, with 9/14 (64%) patients with Stage I or II ATTR CA remaining free of recurrent arrhythmia compared to only 1/10 (10%) patients with Stage III disease ( P  = 0.005). Death occurred in 7 (29%) patients in the ablation group compared to 36 (75%) in the non-ablation arm ( P  = 0.01). Rates of ischaemic stroke were similar in both groups. Ablation was associated with a significant reduction in the frequency of hospitalization for HF/arrhythmia (1.7 ± 2.4 hospitalizations vs. 4 ± 3.5, P  = 0.005). On Cox proportional hazards analyses, ablation was associated with improved survival (hazard ratio 0.38, 95% confidence intervals 0.17–0.86; P  = 0.02). Conclusion: Atrial fibrillation ablation is associated with reduced mortality in ATTR CA and is most effective when performed earlier during the disease process.